2017
DOI: 10.1021/acs.molpharmaceut.7b00505
|View full text |Cite
|
Sign up to set email alerts
|

Systems Pharmacology Dissection of Multiscale Mechanisms of Action for Herbal Medicines in Treating Rheumatoid Arthritis

Abstract: As a chronic inflammatory and angiogenic disease with increased morbidity and mortality, rheumatoid arthritis (RA) is characterized by the proliferation of synovial tissue and the accumulation of excessive mononuclear infiltration, which always results in the joint deformity, disability, and eventually the destruction of the bone and cartilage. Traditional Chinese Medicine (TCM), with rich history of proper effectiveness in treating the inflammatory joint disease containing RA, has long combated such illness f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 98 publications
0
22
0
Order By: Relevance
“…Finally, we used UPLC-Q-Exactive-MS E and GC-MS to analyze the potential ingredients of rougui-fuzi in the treatment of CCVDs. Collectively, herbal medicines always contain huge numbers of ingredients, diversified bioactive compounds of TCM with their related multiple targets, and multiple pathways, making it difficult to uncover the mechanisms of their interactions employing only traditional experimental approaches [70]. Systems pharmacology can offer an integrated system-level method to identify multichemicals, multitargets, and multipathways of Chinese herbs, which provided an alternative to understanding the scientific therapeutic mechanisms of Chinese herbs in treating complex diseases [21,71].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we used UPLC-Q-Exactive-MS E and GC-MS to analyze the potential ingredients of rougui-fuzi in the treatment of CCVDs. Collectively, herbal medicines always contain huge numbers of ingredients, diversified bioactive compounds of TCM with their related multiple targets, and multiple pathways, making it difficult to uncover the mechanisms of their interactions employing only traditional experimental approaches [70]. Systems pharmacology can offer an integrated system-level method to identify multichemicals, multitargets, and multipathways of Chinese herbs, which provided an alternative to understanding the scientific therapeutic mechanisms of Chinese herbs in treating complex diseases [21,71].…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports showed that the TCMSP-based method was reliable for screening out bioactive compounds of TCM for treatment of thrombosis [35], gastric precancerous lesions [36], cardiocerebrovascular disease [37], and rheumatoid arthritis [38]. In this study, 41 bioactive compounds of Quyushengxin formula were selected out by using TCMSP database in combination with ADME properties.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, nanomedicines have been proven an effective way for specific delivery to the site of inflammation in T2T of RA. Meanwhile, the drug‐loading system with specific ligands aims to improve the therapeutic efficiency of RA and reduce damage to normal tissues 26–29. Moreover, compared with conventional treatment, application of nanomaterial‐based drugs in T2T of RA achieves better therapeutic outcomes and saves more costs in the long run.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the drug-loading system with specific ligands aims to improve the therapeutic efficiency of RA and reduce damage to normal tissues. [26][27][28][29] Moreover, compared with conventional treatment, application of nanomaterial-based drugs in T2T of RA achieves better therapeutic outcomes and saves more costs in the long run. A previous study has reported that liposomes loading GC to the inflamed joints can enhance the antiinflammatory activity in RA treatment.…”
mentioning
confidence: 99%